KURIKULUM PAI YANG MEMBEBASKAN SEBAGAI JAWABAN ATAS DEKADENSI NALAR KEAGAMAAN SISWA - Muhammad Syauqi (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
The weakening of students’ religious reasoning has become a serious concern in Islamic education. Students tend to interpret religious teachings dogmatically and literally, with minimal critical or reflective thought. This leads to exclusive attitudes and limited adaptability to social change. This condition is further exacerbated by the indoctrinative approach of the current Islamic Religious Education (IRE) curriculum, which often lacks dialogical engagement and intellectual empowerment. This study aims to analyze how a liberating IRE curriculum can serve as an alternative strategy to reconstruct students’ religious reasoning that is critical, inclusive, and contextual. Using a qualitative approach through field study at SMA Negeri 3 Banda Aceh, data were collected via observation, interviews, and document analysis, and examined through descriptive-analytical techniques. The findings reveal that a more dialogical, reflective, and humanistic PAI curriculum fosters students’ critical thinking, enabling them to not only accept religious values passively but also question, internalize, and actualize Islamic principles in daily life. The theoretical contribution of this study lies in its proposal of an emancipatory curriculum model grounded in Islamic ethical values. Meanwhile, its practical contribution provides direction for future curriculum reforms in Islamic education across Indonesia.